A review of Paratranes Zimmerman, 1994, Xanthorrhoea-associated weevils of the Tranes group (Coleoptera, Curculionidae, Molytinae), with description of a new species - Hsiao, Yun; Oberprieler, Rolf G. (European Journal of Taxonomy, 2021)
Grasstrees (Xanthorrhoea) are a group of monocotyledonous plants endemic to Australia, with a characteristic crown of long and narrow leaves. In the present study, the grasstree-associated weevils of the genus Paratranes Zimmerman, 1994 are reviewed and two species are recognised: P. monopticus (Pascoe, 1870) and P. zimmermani sp. nov. A lectotype for Tranes xanthorrhoeae Lea, 1898, which was recently synonymised with P. monopticus, is herein designated, and the validity of this synonymy is confirmed. Descriptions and diagnoses of the species are supplemented with photographs of their habitus and salient structures as well as a map of their distributions.